Lichens as bioindicators of air quality in mining areas of Latin America, with special reference to Catamarca, Argentina - Cañas, Martha Susana (2017)
Fil: Cañas, Martha Susana. Universidad Nacional de Catamarca. Facultad de Tecnología y Ciencias Aplicadas; Argentina.